The metabolic cost of balance in cycling - Miller, A. I.; Heath, E. M.; Bressel, E.; Smith, G. A. (Journal of Science and Cycling, 2013)
Ergometers and stationary bicycle trainers are commonly used in laboratories to simulate overground riding. Missing from such instrumentation, however, is any demand for balance and the fraction of the metabolic cost associated with dynamic balance. An alternative training device, rollers, may provide a more ecologically valid simulation of overground riding because dynamic balance is required. The purpose of this study was to compare oxygen consumption (VO2) at a similar power level during cycling on an ergometer, trainer, and rollers. Highly-trained cyclists (n = 7, VO2 peak = 65 ± 5 mL/kgmin) performed a VO2 peak test on a trainer using their own bicycles, followed by 4 min sub-max tests at a power corresponding to 74.1 ± 4.3% of VO2 peak on three cycling devices in randomized order. On rollers and stationary trainer, power was measured via a Power Tap SL+ hub and on the ergometer, using resistance. Matching of mechanical power across all 3 modes, as it correlates to VO2 was accomplished using linear regression based on the VO2 peak test. Mean VO2 values at constant power levels were: rollers = 49.2 ± 5.2, trainer = 48.0 ± 5.2, and ergometer = 48.0 ± 4.8 mL/kgmin. Riding on rollers required 2.5% greater VO2 compared to riding a stationary trainer or ergometer at the same mechanical power level (p < 0.05). This increase was likely due to the metabolic cost of balance associated with cycling on rollers and suggests that rollers may better simulate the metabolic cost of overground cycling at approximatlye 70% of VO2 peak.